Correction: Youssef et al. Phytochemical Analysis and Profiling of Antitumor Compounds of Leaves and Stems of Calystegia silvatica (Kit.) Griseb. Molecules 2023, 28, 630 - Ahmed M. M. Youssef; Doaa A. M. Maaty; Yousef M. Al-Saraireh (Molecules, 2023)
There were errors in the original publication [...]